EFEKTIVITAS DESAIN BERBASIS MODEL PEMBELAJARAN INQUIRY DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Shella Dyah Wulansari; Een Yayah Haenilah; Caswita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of inquiry-based learning model design with a realistic approach to improve students' critical thinking skills. The learning design was developed using the Borg and Gall design consisting of 10 development steps. The sample in this study were students of class IVA and IVB SDN 55 Gedong Tataan Pesawaran totaling 26 students in each class. Class IVA as the experimental class and class IVB as the control class. The results of the N-Gain test conducted obtained a value of 0.64 in the experimental class with a moderate category and 0.42 in the control class with a moderate category. The results of the independent sample t-test conducted by comparing the pretest values ​​of the experimental and control classes obtained a sig. value of 0.236> 0.05, which means H0 is rejected so that it can be concluded that there is no significant difference in the pretest values ​​of the experimental and control classes. The test results on the posttest value obtained a sig. value of 0.001<0.05, which means H1 is accepted so that it can be concluded that there is a significant difference between the average values ​​of the experimental and control classes